Nerval`s voyage to the world of the dead - Pinto, Maria Cecília de Moraes (Lettres Françaises, 2008)
Gérard de Nerval weaves, throughout the years, a web of texts which will lead to his enigmatic Aurélia – a fragmented narrative of a long voyage to the world of the dead, intermingled with returns to the real.